(3cTa GdfbGH Yf GdeSGFd GdUYGHs - (3eMeO Hf YHO GdhgGH Hf OGhO GdgeOGfj GdcGXej EeGe GdMQejf,J (B1305 (3g` s
(3ChdgG (B:s
(3Cf CRci eG JMedg HWhf GdOaGjQ s
(3BNQgG (B:s
(3aGdMeO ddg GdPi habfG ddLhGH hCdgefG GdUhGH ai cTa GdfbGH Yf gPg GdeSGFd GdUYGH s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeYGQa GdYGeIs